Profil Spesies Candida Dan Pola Kepekaan Antijamur Pada Pasien Candidemia Darah di Unit Mikrobiologi Klinik RSUD Dr.Soetomo periode 2020-2023 - Faizah, Wardatun; Wiqoyah, Nurul; Ervianti, Evy; Endraswari, Pepy Dwi (Universitas Pahlawan Tuanku Tambusai, 2024)
Candida spp fungal infections. can attack the circulatory system (can be known as candidemia or blood infection by the fungus Candida spp.). Patients in the intensive care unit (ICU) or emergency unit (IGD) with long-term air-conditioned conditions resulting in Candida spp. can grow more easily and increase the risk of fungal infections. This study aims to evaluate the profile of Candida spp. as well as patterns of sensitivity to antifungals in patients with blood candidemia in the Clinical Microbiology Unit of Dr. RSUD. Soetomo during the 2020-2023 period. This research method involves analysis of medical record data of patients diagnosed with blood candidemia, with a retrospective descriptive research type. The research samples were isolate data, used were clinical specimens that can cause candidiasis in the vagina, oral cavity and urogenital tract. The sample size in this study was as large as the data from isolates originating from a total of clinics in the time period. The results of this study provide a comprehensive picture regarding the distribution of Candida spp. the most commonly encountered, as well as the pattern of sensitivity to certain antifungals in patients with blood candidemia in the Dr. Hospital environment. Soetomo. It is hoped that the information obtained from this study will provide better guidance in the management and selection of appropriate therapy for patients affected by blood candidemia in the future.